The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1037/1076-8998.7.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Työhön Job Search Program in Finland: Benefits for the unemployed with risk of depression or discouragement.

Abstract: The impact of preventive interventions for the unemployed may vary depending on the context of the labor policies and benefit systems of the country where it is implemented. The Työhön Job Search Program was based on a method developed in the United States for recently unemployed workers. This study examined outcomes of the intervention in the context of the European labor market for participants who had been unemployed for a longer period. A total of 1,261 unemployed Finnish job seekers participated in a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 22 publications
4
123
0
7
Order By: Relevance
“…The Työhön Job Search Program is almost identical to the 20-hr MPRC program but includes some minor adaptations. The Työ-hön program showed beneficial effects similar to those of the U.S. MPRC Job Search Program and demonstrated that the intervention program is also beneficial to longer term unemployed workers (Vuori & Silvonen, 2005;Vuori et al, 2002). A study by Vuori and Vinokur (2005) demonstrated this mediating role of job-search self-efficacy and inoculation against setbacks for mental health and reemployment outcomes.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The Työhön Job Search Program is almost identical to the 20-hr MPRC program but includes some minor adaptations. The Työ-hön program showed beneficial effects similar to those of the U.S. MPRC Job Search Program and demonstrated that the intervention program is also beneficial to longer term unemployed workers (Vuori & Silvonen, 2005;Vuori et al, 2002). A study by Vuori and Vinokur (2005) demonstrated this mediating role of job-search self-efficacy and inoculation against setbacks for mental health and reemployment outcomes.…”
mentioning
confidence: 85%
“…Often job-search training is an adaptation of some program or a compiled mixture of many programs or has no specific theoretical foundation. In previous studies, job-search training has generally shown positive effects on reemployment, quality of reemployment, and mental health (Dolton & O'Neill, 2002;Rife & Belcher, 1994;Vinokur, Price, & Schul, 1995;Vuori, Silvonen, Vinokur, & Price, 2002). However, little is known about the role that the applied training techniques play in these effects.…”
mentioning
confidence: 99%
“…The Työhön Job Search Programme is a Finnish version of the JOBS programme (Vuori et al, 2002;Vuori & Silvonen, 2005) which examined the programme in the context of a European labour market for individuals who had been unemployed for a longer period (mean = 10.7 months). At the two-year follow-up, significantly more of the experimental group were re-employed, in subsidised work or in vocational training (70.4%) than the control group (64.1%).…”
Section: Previous Studies Of the Jobs Programmementioning
confidence: 99%
“…Most notable is the work of the Michigan Prevention Research Center (MPRC) who developed a group based job search training intervention for unemployed adults. They produced evidence of positive impacts on mental health variables as well as employment outcomes (Price, Vinokur & Friedland, 2002); these findings have been replicated internationally, notably in Finland (e.g Vuori, Silvonen, Vinokur & Price, 2002). This work was developed from the outset with the intention of creating a preventive public mental health intervention (e.g.…”
Section: Evidencementioning
confidence: 99%